A comparison of two micro-beam X-ray emission techniques for actinide elemental distribution in microscopic particles originating from the hydrogen bombs involved in the Palomares (Spain) and Thule (Greenland) accidents - Jiménez-Ramos, M. C.; García López, J.; García-Tenorio, R.; Holm, Elis (Spectrochimica Acta Part B: Atomic Spectroscopy, 2010)
In order to validate and to gain confidence in two micro-beam techniques: particle induced X-ray emission with nuclear microprobe technique (μ-PIXE) and synchrotron radiation induced X-ray fluorescence in a confocal alignment (confocal SR μ-XRF) for characterization of microscopic particles containing actinide elements (mixed plutonium and uranium) a comparative study has been performed. Inter-comparison of the two techniques is essential as the X-ray production cross-sections for U and Pu are different for protons and photons and not well defined in the open literature, especially for Pu. The particles studied consisted of nuclear weapons material, and originate either in the so called Palomares accident in Spain, 1966 or in the Thule accident in Greenland, 1968. In the determination of the average Pu/U mass ratios (not corrected by self-absorption) in the analysed microscopic particles the results from both techniques show a very good agreement. In addition, the suitability of both techniques for the analysis with good resolution (down to a few μm) of the Pu/U distribution within the particles has been proved. The set of results obtained through both techniques has allowed gaining important information concerning the characterization of the remaining fissile material in the areas affected by the aircraft accidents. This type of information is essential for long-term impact assessments of contaminated sites. © 2010 Elsevier B.V. All rights reserved. This work has been supported by the Junta de Andalucia Excellence Project RNM 135 (TU-DRAMA — Ultra-sensitive techniques for radionuclides determination in environmental materials). Peer Reviewed